Seed Number and 100‐Seed Weight of Pearl Millet (Pennisetum glaucum L.) Respond Differently to Low Soil Moisture in Genotypes Contrasting for Drought Tolerance. Issue 2 (30th December 2013) - Aparna, K.; Hash, C. T.; Yadav, R. S.; Vadez, V.
Abstract Water stress after flowering, one of the major factors limiting yields of pearl millet, affects both seed setting and grain filling and is a consequence of more/less water used prior to anthesis. However, whether genotypes have different sensitivities for seed setting and filling under drought, if exposed to similar stress intensity, is unclear. Experiments were conducted in two pairs of pearl millet genotypes, that is, PRLT2/89‐33 and H77/833‐2, 863B and 841B, contrasting for terminal drought tolerance, and two genotypes, ICMR 01046 and ICMR 01029 (IL‐QTLs), introgressed with a terminal drought tolerance QTL from PRLT2/89‐33 into H77/833‐2. Total seed weight, panicle number, 100‐seed weight, seed number and stover biomass were measured at different soil moistures and throughout grain filling. Sensitive H77/833‐2 had higher seed number and yield under well‐watered (WW) conditions than in PRLT2/89‐33 and IL‐QTLs. Upon increases in water stress intensity, H77/833‐2 suffered losses mostly in stover biomass (45 %) and seed number (60 %) at 0.3 FTSW whereas the biomass and seed number of PRLT2/89‐33 decreased little (20 % and 25 %). The 100‐seed weight of H77/833‐2 decreased only 20 % under stress. Tolerant 863B also maintained a higher seed number and biomass under water stress than 841B. Grain filling duration in PRLT2/89‐33 and IL‐QTLs was similar to that of H77/833‐2 under WW conditions but lasted longer than in H77833‐2 under water stress (WS). Similarly, seed growth of 863B was longer than 841B under WS. It is concluded that the higher seed yield of tolerant parents PRLT2/89‐33 and 863B, and of IL‐QTLs under WS was explained by the retention of a higher number of seeds than in sensitive lines, while the decrease in the 100‐seed weight was proportionally less than the decrease in seed number. Phenotype with lesser number and larger size of panicles and larger grain size, like genotypes PRLT2/89‐33 and 863B, withstood post‐anthesis water stress better. IL‐QTL inherited part of these characteristics, indicating a role for the terminal drought QTL in maintaining larger seed number and higher 100‐seed weight. The continuous stover biomass increase under WW in H77/833‐2, due to tillering, might indicate that tiller growth and grains are in competition for resources after anthesis, and this may relate to the relatively shorter grain‐filling period.